Hot Student Stories

# Match the circle equations in general form with their corresponding equations in standard form. Not all will be used. x2 + y2 − 4x + 12y − 20 = 0 (x − 6)2 + (y − 4)2 = 56 x2 + y2 + 6x − 8y − 10 = 0 (x − 2)2 + (y + 6)2 = 60 3x2 + 3y2 + 12x + 18y − 15 = 0 (x + 2)2 + (y + 3)2 = 18 5x2 + 5y2 − 10x + 20y − 30 = 0 (x + 1)2 + (y − 6)2 = 46 2x2 + 2y2 − 24x − 16y − 8 = 0 x2 + y2 + 2x − 12y − 9 = 0

#### 1 answer

### Add you answer

##### Wanna comment?

Please Sign In / Sign Up

The standard form of the equation of a circle is given by the following expression: On the other hand, the general form is given as follows:this way, we can sort the above equations in the following way: Equations in Standard Form: Equations in the General Form: So let's match each equation:Then its general form is:in the First place. (a) the parties of 5) Then its general form is: Second. (b) the parties 1) Then its general form is:Third. (c) the parties 3)Below, its general form is: Fourth. d) the matches out of 6)